Rapid cessation of acute diarrhea using a novel solution of bioactive polyphenols: a randomized trial in Nicaraguan children - Arthur Dover; Neema Patel; KT Park (PeerJ, 2015)
Goal. We assessed the effectiveness of bioactive polyphenols contained in solution (LX) to restore normal bowel function in pediatric patients with acute diarrhea.Background. While providing oral rehydration solution (ORS) is standard treatment for diarrhea in developing countries, plant-derived products have been shown to positively affect intestinal function. If a supplement to ORS resolves diarrhea more rapidly than ORS alone, it is an improvement to current care.Study. In a randomized, double-blind, placebo-controlled cross-over study, 61 pediatric patients with uncontrolled diarrhea were randomized to receive either ORS + LX on day 1 and then ORS + water on day 2 (study arm) or ORS + water on day 1 and then ORS + LX on day 2 (control arm). Time to resolution and number of bowel movements were recorded.Results. On day 1, the mean time to diarrhea resolution was 3.1 h (study arm) versus 9.2 h (control arm) (p = 0.002). In the study arm, 60% of patients had normal stool at their first bowel movement after consumption of the phenolic redoxigen solution (LX). On day 2, patients in the study arm continued to have normal stool while patients in the control arm achieved normal stool within 24 h after consuming the test solution. Patients in the control arm experienced a reduction in the mean number of bowel movements from day 1 to day 2 after consuming the test solution (p = 0.0001). No adverse events were observed.Conclusions. Significant decreases in bowel movement frequency and rapid normalization of stool consistency were observed with consumption of this novel solution.